Islamic Educational Values in the Bedikekh Culture of the Liwa Community of West Lampung - Elfira Sari; Syafei, Imam; Hijriyah, Umi; Baharudin, Baharudin; Asyha, Agus Faisal (Seutia Hukamaa Cendekia, 2024)
The values ​​of Islamic education are everything in which there are positive elements that are beneficial for humans to develop human knowledge and insight both in the cognitive, affective and psychomotor domains so that they can develop optimally in accordance with Islamic teachings in the form of norms and rules contained in Islamic education, such as morals, faith and worship. Bedikekh culture is a custom that developed among the Lampung Saibatin community, namely an art in the form of chanting poetry of praise to Allah taken from the book of barzanji accompanied by musical drums together. In this case, the researcher wants to know the values ​​of Islamic education contained in the bedikekh culture of the Liwa people of West Lampung, which aims to see whether this bedikekh culture is in line with Islamic teachings or deviates from Islamic teachings and provides an understanding of the procession and meaning of bedikekh culture. Researchers try to find the realm of Islamic educational values ​​in bedikekh culture. This research uses qualitative research methods. The data was obtained using several data collection techniques, including interviews, observation and documentation. Then, after the data was collected, the researcher analyzed it by reducing, presenting, and drawing conclusions from the data. Furthermore, the validity of the data in this research uses source, time and model triangulation techniques. This research shows Islamic educational values ​​in the bedikekh culture of the Liwa people of West Lampung. The educational values ​​instilled indirectly are in the form of good morals, such as respecting each other/respecting/not being selfish, polite, helpful, patient, trustworthy and disciplined. The attitude of the members of the bedikekh participants is to follow these morals. This research also explains the supporting and inhibiting factors for bedikekh practice so that readers can better understand what bedikekh culture is